PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA WALL CHART TERHADAP KEMAMPUAN MENULIS PARAGRAF ARGUMENTASI SISWA KELAS 4 SEKOLAH DASAR - Oktaviana, Nur; Azmy, Bahauddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low ability of fourth-grade students at SDN Keboananom Sidoarjo in writing argumentative paragraphs. The study was conducted to understand the effects of the Problem-Based Learning model supported by wall chart media on students' argumentative paragraph writing skills. The research approach used was quantitative, with a quasi-experimental category and a posttest-only control group design. The population of this study included all fourth-grade students, while the respondents were students from classes 4A and 4B, totaling 28 students. Data collection was carried out using a posttest and analyzed statistically through normality tests, homogeneity tests, and hypothesis testing using a t-test. Based on the research findings, it can be concluded that the Problem-Based Learning model, supported wall chart, had an impact on the ability of fourth-grade students at SDN Keboananom Sidoarjo to write argumentative paragraphs. The data analysis results showed a significance value (sig. 2-tailed) of 0.000, which is <0.05, indicating that Ho was rejected and Ha was accepted.